PTH-055 A 17-year prospective cohort study of paediatric inflammatory bowel disease patients diagnosed less than 10 years of age (paris a1a). (22nd June 2015) - Henderson, P; Rogers, P; Wilson, DC
Abstract : Introduction: The recently published paediatric inflammatory bowel disease (PIBD) Paris classification highlights that patients diagnosed before their 10 th birthday (Paris A1a) have a different clinical phenotype at presentation than those diagnosed aged 10–16 years (A1b). However, data regarding accurate incidence rates, disease natural history, medication use and surgery in the A1a group is lacking. Method: All A1a PIBD patients within our prospective, regional PIBD database from South-East Scotland (SES) diagnosed from 08/97–07/14 had data recorded regarding demographics, phenotype data, details of medical therapy and surgery; data at last paediatric follow-up (FU) was also collected. Accurate incidence data was generated using publicly available population data for SES. Statistics were performed in GraphPad Prism and R with Poisson regression analysis for incidence data. Results: 121 A1a PIBD patients (77 Crohn's disease [CD], 28 ulcerative colitis [UC] and 16 IBD-unclassified [IBDU]) were identified in the 17 yr period (31% of entire PIBD cohort); 52% were male. Median FU was 7.1yrs (IQR 3.6–9.6). The incidence of A1a PIBD during 2000–2013 was 4.4/100, 000/yr (CD 2.8/100, 000/yr; UC 1.0/100, 000/yr; IBDU 0.6/100, 000/yr); there was no significant increase in incidence between 2000–2006 and 2007–2013 (p = 0.577). At diagnosis 20% of CD patients diagnosed at 2–5 yrs had panenteric disease, 36% isolated colonic disease, and 16% had isolated oral and/or perianal disease; all had inflammatory behaviour. At prolonged FU phenotype was stable. In the older CD cohort (6–9 yrs) 41% had panenteric disease at diagnosis (45% at FU), 25% had isolated colonic disease, and 17% of this group progressed to penetrating/fistulising disease at follow-up. The older age-group were more likely to have panenteric disease at diagnosis (p = 0.002) or progress to penetrating disease (p < 0.001). A1a patients were exposed to immunosupressive therapy and had surgery performed later after diagnosis than A1b patients (p < 0.05); successful remission at anti-TNF therapy induction was achieved in 57% of patients. 20 patients (17%) had IBD-related surgery while in paediatric services. Conclusion: A third of patients are diagnosed with PIBD present before 10 years of age, with the incidence of very early-onset disease remaining stable in recent years. The requirement for immunosuppression, especially biological therapy, is significant and represents a high disease burden in these patients. Intriguingly, differences exist between those diagnosed at 6–9 years in that they are exposed to immunosuppressants and undergo surgery sooner after diagnosis and are more likely to have panenteric CD at diagnosis and to progress to penetrating disease. Disclosure of interest: None Declared.